Piezo1 protects against inflammatory bone loss via a unique Ca2+-independent mechanism in osteoclasts - Shindo, Satoru; Nakamura, Shin; Hawthorne, Avery; Heidari, Alireza; Pastore, Maria Rita; Okamoto, Motoki; Suzuki, Maiko; Salinas, Manuel; Memida, Takumi; Minond, Dmitriy; Bontempo, Alexander; Cayabyab, Mark; et al. (Frontiers in Immunology, 2025)
IntroductionBone integrity relies on mechanical stimulation, and its absence, such as in disuse osteoporosis or periodontitis, enhances osteoclast-mediated resorption. Although Piezo1 is a well-characterized mechanosensitive ion channel in several cell types, its function in osteoclast lineage cells has remained unclear.MethodsWe examined Piezo1 expression and signaling in pre-osteoclasts (OCs) using mouse models of periodontal bone loss and in vitro differentiation assays. Genetic and pharmacological approaches were applied to manipulate Piezo1 activity. Downstream pathways were assessed with a focus on NFATc1 regulation, Akt phosphorylation, and PP2A activity. The therapeutic potential of the Piezo1 agonist Yoda1 was tested in inflammatory bone loss models.ResultsPiezo1 was selectively expressed and functional in pre-OCs, where it acted as a mechanosensor to inhibit RANKL-induced OC-genesis. Activation of Piezo1 suppressed NFATc1 via a Ca2+-independent mechanism involving PP2A-mediated dephosphorylation of Akt, distinct from the canonical Ca2+-calcineurin pathway. In healthy periodontal bone, Piezo1 restrained osteoclast differentiation under mechanical loading, preserving bone mass. During periodontitis, reduced mechanical forces impaired Piezo1 function, resulting in unchecked osteoclast activation and pathological resorption. Pharmacological activation of Piezo1 with Yoda1 restored the anti-resorptive pathway and effectively prevented inflammatory bone loss, even in the absence of mechanical input.DiscussionOur findings redefine Piezo1 as a critical mechanosensor in pre-OCs and establish the Piezo1-PP2A-Akt axis as a novel regulator of NFATc1-driven OC-genesis. These results provide a mechanistic explanation for bone resorption in mechanically compromised states and highlight Piezo1 activation as a therapeutic strategy to mimic mechanical cues and suppress pathological OC-genesis in conditions such as periodontitis, rheumatoid arthritis, and osteoporosis.